Effects of Aerobic, Resistance, and Combined Exercise Training on Psychiatric Symptom Severity and Related Health Measures in Adults Living With Schizophrenia: A Systematic Review and Meta-Analysis - Bredin, Shannon S. D.; Kaufman, Kai L.; Chow, Maddison I.; Lang, Donna J.; Wu, Nana; Kim, David D.; Warburton, Darren E. R. (Frontiers in Cardiovascular Medicine, 2022)
Previous research has demonstrated the efficacy, effectiveness, and safety of exercise training in persons living with schizophrenia. However, the optimal exercise training program remains unclear. The aim of this paper was to conduct a systematic review and meta-analysis of the effects of aerobic, resistance, and combined aerobic and resistance training on health-related physical fitness and positive and negative symptoms in persons living with schizophrenia. Six electronic databases were searched systematically from their inception to December 2020 [MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, SPORTDiscus, and Cumulative Index to Nursing and Allied Health Literature (CINAHL)] to identify literature examining the effects of exercise training on psychiatric symptoms and health-related physical fitness indicators in persons living with schizophrenia. A total of 22 studies (n = 913) were included in this review, and 12 studies (n = 554) included within the meta-analysis reported the effects of exercise training (aerobic, resistance, and combined aerobic and resistance) in persons living with schizophrenia. Aerobic training had a significant decrease on Positive and Negative Syndrome Scale (PANSS) negative scores (ES −2.28, 95% CI −3.57 to −1.00; p = 0.0005) and PANSS general scores (ES −2.51, 95% CI −3.47 to −1.55; p < 0.00001). Resistance training did not lead to significant effects on PANSS total scores. Combined aerobic and resistance training did not lead to significant changes in body mass index, PANSS positive scores, or PANSS total scores. However, grouping together the results from all exercise training modalities (including aerobic training, resistance training, and combined aerobic and resistance training) revealed significant effects on body mass index (ES 1.86, 95% CI 0.84 to 2.88; p = 0.0003), maximal/peak oxygen consumption (ES 2.54, 95% CI 1.47 to 3.62; p = < 0.00001), body weight (ES 6.58, 95% CI 2.94 to 10.22; p = 0.0004), PANSS negative scores (ES −1.90, 95% CI −2.70 to −1.10; p < 0.00001), and Scale for the Assessment of Negative Symptoms (SANS) total (ES −14.90, 95% CI −22.07 to −7.74; p < 0.0001). Collectively, these findings support the importance of exercise participation (aerobic and resistance training) in persons living with schizophrenia.